Direct Imaging of Plant Metabolites in the Rhizosphere Using Laser Desorption Ionization Ultra-High Resolution Mass Spectrometry - Lohse, Martin; Haag, Rebecca; Lippold, Eva; Vetterlein, Doris; Reemtsma, Thorsten; Lechtenfeld, Oliver J. (Frontiers in Plant Science, 2021)
The interplay of rhizosphere components such as root exudates, microbes, and minerals results in small scale gradients of organic molecules in the soil around roots. Current methods for a direct chemical imaging of plant metabolites in the rhizosphere often lack molecular information or require labeling with e.g. fluorescent tags or isotopes. Here we present a novel workflow using laser desorption ionization (LDI) combined with mass spectrometric imaging (MSI) to directly analyze plant metabolites in a complex soil matrix. Undisturbed samples of the roots and the surrounding soil of Zea mays L. plants from either field- or laboratory-scale experiments were embedded and cryosectioned to 100 µm thin sections. Target metabolites were detected with a spatial resolution of 25 µm in the root and the surrounding soil based on accurate masses using ultra-high mass resolution laser desorption ionization Fourier-transform ion cyclotron resonance mass spectrometry (LDI-FT-ICR-MS). Using this workflow, we could determine rhizosphere gradients of a dihexose (e.g. sucrose) and other plant metabolites (e.g. coumaric acid, vanillic acid). Molecular gradients for the dihexose showed a high abundance of this metabolite in the root and a strong depletion of the signal intensity within 150 µm from the root surface. Analyzing several sections from the same undisturbed soil sample allowed us to follow molecular gradients along the root axis. In addition, benefiting from the ultra-high mass resolution isotopologues of target metabolites could be readily resolved to enable the detection of stable isotope labels on the compound level. Overall, direct molecular imaging via LDI-FT-ICR-MS allows for the first time a non-target or targeted analysis of plant metabolites in undisturbed soil samples paving the way to study the turnover of root-derived organic carbon in the rhizosphere with high chemical and spatial resolution.